PROSEDUR PELAKSANAAN KESELAMATAN DAN KESEHATAN KERJA PADA PEKERJA INDUSTRI KOTA TOMOHON - Lumowa, Fresy Nissia (JURNAL ILMIAH KESEHATAN MANADO, 2024)
Occupational Safety and Health (K3) is a guideline that must exist in every workplace, as regulated in Law Number 1 of 1970 concerning Occupational Safety where every workplace is obliged to carry out Occupational Safety and Health procedures which aim to fulfill the need for a sense of security. and comfortable while working. Objective To find out procedures for implementing Occupational Safety and Health in the workplace. Method using qualitative methods with in-depth interview techniques with 7 informants. Results is industrial workers have a good view of occupational safety and health, this can be seen from the statement given by the informant which states that occupational safety and health is an important thing to implement in the workplace and must be paid attention to by the work owner. The company has carried out outreach activities related to work safety, in this case Basic Life Support Training (BHD), but not all workers participated in it due to limited funds provided by the company. The way work in the production process is carried out is based on the company's production process SOP and does not refer to Standards. K3 Operational Procedures (SOP) so that errors often occur in their implementation and sometimes do not meet production achievements, the production process is coordinated by field coordinators, not General Occupational Safety and Health (K3) expert officers in accordance with the provisions of the applicable laws. Conclusion: Workers carry out production process procedures in accordance with the provisions and standards issued by the work owner, do not apply work method SOPs based on occupational safety and health elements. In their activities, workers use machines that they themselves have learned how to work, so they often experience errors and even work accidents due to incorrectly operating machines and tools, work owners provide Personal Protective Equipment (PPE) but it does not comply with K3 standards, and its availability is lacking so that not all Production workers use PPE.